Teaching Russian As A Foreign Language Using Modern Methods - Talipova Dilfuza Khamidovna (Euro Asian Journal Publishing, 2024)
This article discusses innovative methods and techniques of teaching the Russian language in order to increase the effectiveness of the learning process. The prospects of using new methods in the formation of conditions for improving the activity of students' learning activities are proved.
Keywords: teaching method; problem-based learning; project-based